WORK AND LIVES IN MAKASSAR COASTAL COMMUNITY: ASSESSING THE LOCAL GOVERNMENT POLICY - Sakharina, Iin Karita; Daud, Aidir Amin; Hasrul, Muh.; Kadarudin, Kadarudin; Assidiq, Hasbi (Hasanuddin Law Review, 2020)
The Makassar City Regional Government formulated a policy that previously carried out Mapping conducted on the less prosperous Coastal community, so departing from the mapping results obtained then formulated a policy as in the development of human resources will be carried out in areas that most need to become a poverty pouch. Local government is the most relevant party to be responsible for increasing the budget. All components, which are responsible for improvement, for the Coastal community, and of course for all parties, who are responsible for improving the welfare of the Coastal community, each related agency provides a budget that is appropriate to the community's needs and the duties and functions of each of the relevant agencies. . In addition, it is in the interests of government policies that harm the Coastal community. The implementation of the reclamation policy which is detrimental to fisheries is of course counterproductive to other policies aimed at the welfare of the Coastal community.